Family inherited, prenatal and perinatal risk factors in Cuban children with primary autism - Daniel Quintana Hernández; Paulina Araceli Lantigua Cruz; Teddy Osmin Tamargo Barbeito; Yohandra Calixto Robert; Nancy Hernández Hernández (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: Primary autism is a heterogeneous neurobehavioral disorder of uncertain etiology in which both genes and the environment contribute to the pathogenesis of the disorder. Objective: To identify family inherited, prenatal and perinatal risk factors in Cuban children with primary autism. Material and Methods: An observational case-control study (1:1) was carried out in children with primary autism, treated at "Juan Manuel Márquez" Pediatric Hospital, Havana, in the period from October of 2014 to September of 2019. The sample was made up of 126 cases and 126 controls. Data on neuropsychiatric diseases, prenatal and perinatal history of three generations were collected. Multivariate logistic regression was performed to identify risk factors related to primary autism. Results: The odds of presenting primary autism were approximately seven and four times higher in children of mothers and fathers of advanced ages, respectively. A history of language disorders and epilepsy in first-degree relatives conferred 27- and 24-fold higher odds of presenting with autism, respectively. The odds of presenting autism were approximately ten times greater in children born to pregnant women with anemia, eight times in children born to pregnant women who had bleeding during pregnancy, and 18 times in those born to mothers with a history of pregestational diabetes mellitus. Conclusions: The history of inherited neuropsychiatric diseases and prenatal and perinatal environmental factors related to hypoxemic events are risk factors for primary autism in the sample of Cuban children studied.